(untitled) (Journal of the College of Basic Education, 2022)
Delayed cognitive bias is an action or act we unconsciously take to document the perspectives and information that feed those information we already have, while at the same time rejecting or ignoring opinions that threaten our view or convictions about the world and everything related to our beliefs and habits, even if The information before us was logical and based on research and scientific facts, and the truth is that the bias of hindsight hinders the person from understanding the nature of what is going on around him, and then makes him reject change and consider him a threat to his security, inner peace and everything he believes in (Moses, 2014, p. 2). Therefore, hindsight bias often distorts our thoughts and beliefs and overestimates the validity of the decisions we make (Passer, et.al, 2008, p.316). Kahneman sees that the hindsight bias is a mistake in thinking and occurs when individuals resort to the process of interpreting and interpreting the world around them and making decisions. Decisions about them are often quick and not subject to thought, and at other times there is too rapid cognitive bias in the decision-making process, which leads to weak and bad decisions (Centeno, 2001:12). Search objective : 1- Building a The level of late-perception bias among educational counselors. 2- Identifying The level of late-perception bias among educational counselors. The researcher built a scale of measure of the educational counselors’ hindsight bias, where the scale consists of (35) paragraphs, against each of which (5) five alternatives are (always apply to me, apply to me often, apply to me sometimes, apply to me rarely, no It applies to me) and extracted the psychometric properties of honesty (discriminative power, internal homogeneity and stability by re-test method, the (Alpha-Cronbach) equation and the statistical indicators of the scale, and verifying the second objective using T-test for one sample. The research reached the following results: Educational counselors have a low level of hindsight bias. To complement the current research, the researcher presented a number of recommendations and suggestions. Giving lectures and holding awareness seminars and workshops to show the importance of the late realization bias of educational counselors by professors specialized in psychological counseling and educational guidance in agreement with the Directorates of Preparation and Training of the Ministry of Education